Isolation and Characterization of a PEG-degrading and Mo-reducing Escherichia coli strain Amr-13 in soils from Egypt (Journal of Environmental Microbiology and Toxicology, 2021)
Molybdenum is a pollutant that shows toxicity to spermatogenesis while polyethylene glycols (PEG) are used predominantly in detergents. The pollution of molybdenum and PEGs are reported worldwide. We have isolated ten molybdenum-reducing bacterial isolates from soil that can reduce molybdenum (sodium molybdate) into the colloidal molybdenum blue (Mo-blue). The screening of these isolates for PEG-degrading ability showed that one isolate was capable to utilize PEG 200, 300 and 600 for optimal conditions were pHs between 5.5 and 8.0, temperatures between 30 and 37 oC, phosphate at 5 mM, molybdate between 10 and 30 mM, and glucose as the electron donor. Biochemical analysis of the bacterium identifies it as Escherichia coli strain Amr-13. Growth was best supported by all PEGs at concentrations of between 600 and 1,000 mg/L. A complete degradation for PEG 200 and PEG 300 at 1,000 mg/L was observed on day four and five, respectively, while nearly 90% of PEG 600 was degraded on day six. The growth of this bacterium on these PEGs was modelled using the modified Gompertz model, and produced growth parameters values, which were maximum specific growth rates of 1.51, 1.45 and 1.18 d-1 and lag periods of 0.53, 0.87 and 1.02 day for PEG 200, PEG 300 and PEG 600, respectively. PEG 200 was the most preferred substrate for this bacterium, while PEG 600 was the least preferred.
Keywords: PEG-degrading; Molybdenum reduction; Molybdenum blue; Escherichia coli; Bioremediation